Caustic ingestion in children in south of Iran. Retrospective study from Shiraz - Iran - Honar, Naser (2017)
Caustic ingestion is a major health concern in both developed and developing countries, that may lead to serious esophageal injury. The clinical presentation of caustic ingestion in children vary from asymptomatic to serious and fatal sequelae, such as perforation and stricture formation. Objective: Due to the lack of a comprehensive study in our area, this study has evaluated clinical and endoscopic manifestations and complications of caustic ingestion in children in south of Iran. Materials and methods: In this retrospective study, we reviewed 75 children with caustic ingestion who admitted in Nemazee Hospital of Shiraz University of Medical Science during 6 years (2006-2011). Sign and symptoms were recorded for each case. Results: The most common symptoms were dysphagia, oral lesions, vomiting, and drooling. Esophageal injuries were detected in both acid and alkali ingestion, but gastric injuries was significantly more in acid ingestion. During follow up period, 20% of all cases developed esophageal stricture. Conclusion: Dysphagia, oral lesions, vomiting, and drooling were the most common findings. Esophageal stricture was found in 20% of cases during 3 months of follow up.